Combatting Islamophobia on the international stage: the need for Muslim unity - Takahashi, Saul Jihad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islamophobia has become the global norm, with governments in many countries blatantly discriminating against Muslims. Islamophobia should be recognized internationally as a violation of international human rights norms, and governments that adopt Islamophobic laws and policies should be held accountable for those violations. Muslim countries should take the lead in raising this issue at international fora, but unity on this front, like on other issues, remains elusive. Nevertheless, recent initiatives by Qatar and Malaysia show promise.